Innovations in Distribution Logistics - Nunen, Jo A.E.E.; Speranza, M. Grazia; Bertazzi, Luca.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
In a globalized economy logistics has become a crucial area for the success of companies. The performance of each company depends on the performance of its suppliers and of its business partners. The customers of each company are spread on a large geographical space. For this reason distribution logistics is the most important and complex part of logistics. An efficient and effective management of distribution logistics is a key issue for the success of a company. There are many different problems to deal with, from facility location to transportation, to inventory management, and, most important, to the integration and optimization of the entire logistics network. Quantitative methods provide relevant tools to support decisions, from strategic to operational, in distribution logistics.
Management Policies in a Dynamic Multi Period Routing Problem -- Optimizing the Storage Area Dimension in a Production System -- On line Routing per Mobile Phone A Case on Subsequent Deliveries of Newspapers -- Service Design Models for Rail Intermodel Transportation -- C.A.s.S.a.n.D.r.A: Computerized Analysis for Supply ChAiN DistRibution Activity -- Ship Routing Scheduling with Persistence and Distance Objecives -- Logistics in Real Time Inventory Routing Operations under Stochastic Demand -- On optimizing production nofed in supply chain systems -- Approximate Optimal Order Batch Sizes in a Parallel aisle Warehouse -- Supply Chain Optimization for the Liquefied Natural Gas Business -- Modeling the Pre Auction Stage The Truckload Case -- Application of the Double Standard Model for Ambulance Location -- A Pricing Algorithm for the Vehicle Routing Problem with Soft Time Windows -- Effective Algorithms for a Bounded Version of the Uncapacitated TPP.
Keywords: Business; Production management; Operations research; Decision making; Applied mathematics; Engineering mathematics; Game theory; Engineering economics; Engineering economy; Business and Management; Operations Management; Operation Research/Decision Theory; Applications of Mathematics; Game Theory, Economics, Social and Behav. Sciences; Engineering Economics, Organization, Logistics, Marketing; Electronic books